Self-Realisation in the Awakening by Kate Chopin - Aaya Adil Alrammah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Racism took a different turn in the 16th century, impacting this generation's society. Through racist beliefs and thoughts, people divided society into divisions. This study was based on racism and white people's historical oppression of black people. In this study, we examined two novels that help to analyze racism in society, and the impact of these novels on culture was also addressed. The study described slavery in the 19th century and the colonial times of Nigerian tribes. Mark Twain’s The Adventures of Huckleberry Finn offered an American perspective on racism vs. the African setting of Things Fall Apart. During the 19th century, Nigerian people faced colonization that impacted the culture and behaviour of indigenous people. In this study, different aspects of racism and the effects of racism on black people were examined. This study also showed that the British invasion forced marginalization in every element of Igbo society, ranging from traditional values to religious and gender roles; this study aims to discuss the differences in the perspective of racism by analyzing Things Fall Apart and The Adventure of Huckleberry Finn. These two pieces of literature helped to develop better concepts and aspects of racism in the social setting and highlighted the racism between white and black people.